A Voltage Sag Generator for Wind Power Generation Using Contactors and IGBTs - QIN Bin; HUANG Hao; WANG Xin (Kongzhi Yu Xinxi Jishu)
In view of the existing transformer form, VSG design scheme is limited by its switch devices, and the voltage sag time can not be accurately controlled. It presented a design scheme of three-phase VSG based on three-phase autotransformer, which used IGBT bidirectional switch and contactor. The IGBT bidirectional switch controls the dropping duration and the starting & stopping phases accurately, and the contactor controls the voltage drop type and the drop depth of the grid. Comparative analysis and experimental results show that the VSG design scheme can simulate various type voltage sags. Compared with the VSG which only uses IGBT as switch device, the scheme can reduce the quantity of IGBT and consequently reduce the cost. Compared with the VSG which only uses contactor as switch device, the VSG with this scheme has better characteristics of voltage drop and recovery of cohesion, which providing favorable conditions for the verification of low voltage ride through capability of wind turbine.